Evaluating the ethicality of sexual consent in films: an empirical reflection - Chow, Nicholas Yiheng (Nanyang Technological University, 2024)
This paper delves into an exploration of sexual consent, particularly its complexities within the context of power dynamics and ethical considerations. It investigates how the expression of consent shapes sexual relationships, examining its manifestations, limitations, and ambiguities. The study is guided by the recognition that the concept of consent is far from straightforward, and that its understanding is muddled by societal norms, linguistic nuances, and power imbalances. The paper provides a response to the #MeToo movement and the evolving discourse surrounding sexual consent in instances of sexual assault, abuse, and harassment. The analysis centers on the portrayal of sexual relationships in three films: The Piano Teacher, Elle, and Tár. These films challenge not only traditional depictions of sexual dynamics but also our understanding of consent. Through these cinematic narratives, the thesis aims to mirror real-life complexities, presenting scenarios that push boundaries and highlight the intersection of ethics, consent, and power. This paper aims to shed light on the multifaceted nature of sexual consent, emphasizing its role as a dynamic force that shapes social relations and especially intimate relationships. By delving into the complexities depicted in films and paralleling them with real-world cases, the research contributes to a more nuanced understanding of consent's intricacies and implications.